2021
DOI: 10.5812/amh.113888
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of High-Intensity Interval Training and Continuous Training on Memory and Correlation with Antioxidant Enzyme Activity in the Rat Brain

Abstract: Objectives: This study aimed to investigate the effects of six-week continuous training (CT) and high-intensity interval training (HIIT) protocols on brain superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPX) activities and their associations with short-, mid-, and long-term memory in albino Wistar rats. Methods: In this study, 18 male albino Wistar rats (5 months old) were randomly assigned to three equal (n = 6) groups of sedentary control (SC), CT, and HIIT. Both CT and HIIT regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It has been observed that muscle and plasma MDA levels, which increase with acute intense exercise, decrease when exercise is continued regularly [19,20,21,22,23]. Although these results are in parallel with many studies, there are studies indicating that resistance exercise significantly increases ROS production [24,25,26].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been observed that muscle and plasma MDA levels, which increase with acute intense exercise, decrease when exercise is continued regularly [19,20,21,22,23]. Although these results are in parallel with many studies, there are studies indicating that resistance exercise significantly increases ROS production [24,25,26].…”
Section: Discussionmentioning
confidence: 89%
“…The high GP-X and CAT activities in all groups in our study indicate that both acute and regular exercise positively affect the antioxidant mechanism. In their study, Chadorneshin et al [23] showed that intense exercise increases CAT and GP-X activities. Lambertucci et al [27] reported that aerobic exercise increased antioxidant enzyme activity in both old and young rats.…”
Section: Discussionmentioning
confidence: 94%
“…Both moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT) modalities of exercise have been shown to decrease the glycosylated form of hemoglobin and fasting blood glucose (FBS) in patients with diabetes [ 13 , 14 ]. However, HIIT training showed better outcomes in reducing FBS and ameliorating hyposensitivity to insulin in adults with diabetes [ 15 , 16 ]. Furthermore, HIIT attenuated glucose and fatty acid metabolism, the respiratory capacity of mitochondria, and ventricular mechano-energetic coupling in cardiac tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Breaking up sedentary behavior with brief bouts of vigorous exercise throughout the day has been proposed as a feasible and efficient approach to improving cardiometabolic health 5 , 6 . Using the term “exercise snacks”, Francois et al 7 demonstrated that brief, intense exercise bouts before main meals improved glycemic control in individuals with insulin resistance.…”
Section: Introductionmentioning
confidence: 99%